Centro de pressão corporal e risco de quedas em pessoas idosas - Albuquerque, Matheus Jacobs de (2018)
The stiffness of the treatment process is an increase in the efficiency of the body system. The main parameters involved in maintaining balance are sensory, nervous and muscular. Any derangement of these parameters may interfere with the individual's balance. The changes are not elevated to the risk of being an adult and increase the risk of occurrence. The objective of this study is to evaluate the relation between body pressure and risk of falls in elderly people. The study is as transversal descriptive-analytical character. The population of the group was composed of three young people and ten people from four groups living in the municipality of Passo Fundo/RS. Data analysis was performed using the Chi-square test, Student's test and analysis of variance. The significance level adopted for the rejection of H0 was = 0.05. Its bones indicate the relationship between the pressure center and the risk of falls or the age group, bat were no associations and sex or body mass index.